PROPOSED INITIATIVES FOR IMPROVING EMPLOYEE ENGAGEMENT IN PT XYZ INDONESIA - Yanuarlin, Marliana
PT XYZ Indonesia, as a part of global XYZ International, Inc. plants, is implementing Integrated Lean Six Sigma (IL6S). IL6S is a strategy to build the capability of the total organization by bringing together Lean, Six Sigma, Total Productive Maintenance (TPM) and High-Performance Work System (HPWS) in an integrated approach. HPWS provides IL6S with sustainability capabilities through 100% employee engagement. The company faced an issue that is decreasing in employee satisfaction and its impact on employee engagement and also on their achieved volume production. This research aims to helps PT XYZ Indonesia increase their employee satisfaction rate and improve employee engagement. In this study the first thing to do was to identify employee survey result that had been conducted in 2017. After that, referred to the employee engagement model of Aon Hewitt, Towers Watson and Deloitte, a conceptual model was created. AHP questionnaire was utilized to determine which employee engagement drivers that need to be prioritized. There were ten participants in managerial level who had been chosen as the decision makers to fill the questionnaire. According to the calculation results, the “Positive Work Environment” criteria got the highest point with 29.8%, and the value of consistency ratio of this calculation is 1.1% or 0.011, it can be assumed that the pairwise matrix of the criteria is reasonably consistent and acceptable. Since the criterion which got the highest weight was “Positive Work Environment”, the alternative priorities of this criterion also were calculated. “Humanistic Workplace” alternative obtained the highest point of priority with 33.3% and the value of consistency ratio is 0.013. Then, to gain an insight about current state of workplace in PT XYZ Indonesia, an interview with ten employee representatives from five departments was conducted. This interview results are used to determine the proposed solution. Based on the calculation result, it can be concluded that to increase the involvement of their employees the company needs to provide more attention in the matter of positive work environment. Thus, PT XYZ Indonesia requires improvement in respect of humanistic workplace. The humanistic workplace is a workplace where employees well-being is getting attention from the employer. The recommendation for the company is to create a well-being program which consists of several initiatives. This well-being program should cover physical wellness, emotional wellness, financial wellness as well as social wellness.